Solution of linear boundary value problems for systems of ordinary differential equations by Godunov’s method - Arushanian, O.B.; Zaljotkin, S.F. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2001)
A numerical algorithm of solving linear boundary value problems for systems of first-order ordinary differential equations is proposed. The algorithm is based on Godunov’s method without storage of intermediate matrices arising during the process of orthogonalization.